Integrated farming system-A means of improving farmers’ well-being in the wetland ecosystem of Bangladesh - Saifun Akter; Jasim Uddin Ahmed; Ismat Ara Begum; Md Abdur Rouf Sarkar; Kanij Fatema; Asif Mahmud; Shijun Ding; Mohammad Jahangir Alam (Farming System)
The wetland ecosystem (Haor) experiences recurrent flooding, which disrupts agricultural activities and impacts farmers' livelihoods annually. Addressing these challenges through integrated farming systems (IFSs) such as Crop ​+ ​Livestock ​+ ​Homestead-Agroforestry, Crop ​+ ​Livestock ​+ ​Fish farming, and Livestock ​+ ​Agroforestry is crucial. However, empirical evidence supporting the economic viability of specific IFSs remains limited. This study aimed to fill this gap by assessing the impact of IFSs on farmers' income and livelihoods in Sunamganj district, Bangladesh. Data from 312 participants collected before (2016) and after (2019) the project's intervention were analyzed using descriptive statistical methods. Farmers in this region readily adopted diverse IFSs, integrating crop cultivation, livestock rearing, vegetable production, agroforestry, fish farming, and open-water fish catching, ensuring efficient resource utilization across enterprises. Predominantly, farmers adopted the Crop ​+ ​Livestock ​+ ​Homestead–Agroforestry ​+ ​Open water fish catching system, which had a benefit-cost ratio (BCR) of 1.40, while the Livestock ​+ ​Homestead–Agroforestry ​+ ​Open water fish catching system demonstrated the highest BCR at 1.58, indicating economic viability. Moreover, the adoption of IFSs led to a statistically significant increase in farming income (p ​< ​0.10), contributing to a notable rise in total income. This adoption also correlated with significant improvements in human and financial capital, indicating a positive transformation in livelihood patterns. Therefore, the findings highlight the potential benefits of IFSs in enhancing farmers' well-being, specifically income and livelihood, and provide valuable insights for policymakers to support the integration of sustainable farming practices in the wetland ecosystem.